THE DESCRIPTION OF CAKE APPLICATION ASSISTANCE TO THE STUDENTS’ ENGLISH SPEAKING SKILL AT SMA SWASTA ST XAVERIUS GUNUNGSITOLI - Giawa, Marinus; Harefa, Afore Tahir Harefa Tahir; Waruwu, Yaredi; Telaumbanua, Kristof Martin Efori (Jurnal Suluh Pendidikan, 2024)
This study aims to describe the assistance of the cake application in learning a speaking skill and to describe the students’ reason for utilizing the cake application in learning the students' speaking skills. The research was conducted in class X at SMA Swasta Santu Xaverius Gunungsitoli with a total of 20 students. The research method used is a qualitative descriptive approach. Data were collected through observations and interviews. The results show that students use the cake application and can utilize the cake application in speaking skill. Students take advantage of it by studying the video menu, conversation dialogue, and path menu. The most frequently utilized by students is the conversation dialogue menu because this menu is very complete. Students can learn speaking, dialogue with native speakers, students can see errors the pronunciation in dialogue sentences, and students are also helped by explanations at the end of the dialogue and equipped with Indonesian translations. However, students also need to actively practice and interact with fellow students and native English speakers